2022
DOI: 10.3390/app12094470
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Solution for Automatic Garment Measurement Using Image Recognition Technologies

Abstract: Global digitization trends and the application of high technology in the garment market are still too slow to integrate, despite the increasing demand for automated solutions. The main challenge is related to the extraction of garment information-general clothing descriptions and automatic dimensional extraction. In this paper, we propose the garment measurement solution based on image processing technologies, which is divided into two phases, garment segmentation and key points extraction. UNet as a backbone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Because so many mistakes can be made while processing clothing manually, it can be challenging. Human inspection does not take defect correlation into account when finding defects [8,9]. The assembly line balancing problem affects sewing lines because of human differences in abilities and efficiency.…”
Section: ░ 1 Introductionmentioning
confidence: 99%
“…Because so many mistakes can be made while processing clothing manually, it can be challenging. Human inspection does not take defect correlation into account when finding defects [8,9]. The assembly line balancing problem affects sewing lines because of human differences in abilities and efficiency.…”
Section: ░ 1 Introductionmentioning
confidence: 99%
“…The presented procedure showed that the implementation of a proper decision-making process requires the constant flow of information exchange between the actors involved, aiming at providing a complete and detailed overview of the operating context. Paulauskaite-Taraseviciene et al [4] presented a methodology based on image processing technologies for automated data extraction. This approach involves two phases-object segmentation and key points extraction-and it is applied to automatically measure the hanging garments disregarding constraints such as space restriction, background requirements, shooting distances, or additional tags needed for measurements.…”
mentioning
confidence: 99%
“…Yu performed intelligent measurement of fish morphological characteristics based on U-Net [37]. Paulauskaite-Taraseviciene measured garments automatically based on U-Net [38]. Li measured the body shapes of goats and cattle under different backgrounds based on U-Net [39].…”
mentioning
confidence: 99%